2022
DOI: 10.3390/foods11101426
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Processing of Liquid Egg Yolks Modulates Physio-Chemical Properties of Mayonnaise

Abstract: In this study, the effect of various heating temperatures (61–70 °C) and times (1–10 min) on physical and chemical properties of liquid egg yolk (LEY) and mayonnaise were investigated. Initially, we found that the increase of LEY protein denaturation was highly correlated with the increase of temperature and time, without causing either protein degradation or aggregation. In addition, the viscosity and particle size of LEY were significantly increased with greater heating temperature and time. Furthermore, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…Among them, a significant decrease in the abundance of 12 phospholipids and a significant increase in the abundance of 12 lysophospholipids, 9 Cers, 1 PA, and 17 related FFAs were observed in the comparison of HEY/FEY (Figure 7A). Similarly, a significant decrease in the abundance of five phospholipids and a significant increase in the abundance of 2 Cers and 12 FFAs were found in the comparison of The TGs in egg yolk are mainly in the form of LDL, as a lipid core wrapped by a phospholipid monomolecular layer [27]. Heat treatment causes denaturation and structural remodeling of LDL, resulting in a change in the state or presence of TGs, which makes it easier for them to be extracted with solvents (methyl tert-butyl ether and methanol mixture, 3:1, v/v).…”
Section: Heat-induced Phospholipid Hydrolysis In Hey and Seymentioning
confidence: 71%
See 2 more Smart Citations
“…Among them, a significant decrease in the abundance of 12 phospholipids and a significant increase in the abundance of 12 lysophospholipids, 9 Cers, 1 PA, and 17 related FFAs were observed in the comparison of HEY/FEY (Figure 7A). Similarly, a significant decrease in the abundance of five phospholipids and a significant increase in the abundance of 2 Cers and 12 FFAs were found in the comparison of The TGs in egg yolk are mainly in the form of LDL, as a lipid core wrapped by a phospholipid monomolecular layer [27]. Heat treatment causes denaturation and structural remodeling of LDL, resulting in a change in the state or presence of TGs, which makes it easier for them to be extracted with solvents (methyl tert-butyl ether and methanol mixture, 3:1, v/v).…”
Section: Heat-induced Phospholipid Hydrolysis In Hey and Seymentioning
confidence: 71%
“…In the process of converting an egg yolk from a liquid to a solid under heat treatment, that is, in the process of forming yolk gel, various physicochemical interactions occur between the components of the egg yolk [ 25 ]. Some studies reported that the aggregation of low-density lipoprotein (LDL) and yolk particles in egg yolk begins to occur at 65–70 °C; however, at this point, a continuous gel was not found to have started to form [ 26 , 27 ]. Therefore, the HEY is still in a fluid form and did not start to form a gel.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The diluted liquid egg yolks were prepared according to the description of Ho et al. (2022) with modifications. The eggshell was lightly tapped with a separator to separate the egg white from the egg yolk.…”
Section: Methodsmentioning
confidence: 99%